Le scénario facteur 4 : les rhétoriques institutionnelles au regard des conduites ordinaires en matière de consommation d’énergie - Olivier Chavanon; Odile Joly; Denis Laforgue; Roland Raymond; Stéphanie Tabois (Développement Durable et Territoires)
The aim of this article is: to point out and to clarify some « gaps » which can be observed between the thinking and acting categories of some public protagonists working towards the Factor 4 scenario, and the reflexive and practical rationalities peculiar to everyday behaviours and to ordinary citizens’ choices as regards energy consumption. This approach will enable us to give an account of ordinary protagonists’ discordant behaviours facing the behaviours expected by public leaders, in another way than postulating these people’s irrationalities or inconstancy. Such an analysis alert to the specific dynamics of populations in their diversity as regards energy consumptions will allow a better understanding of the efficiency limits of public measures in this field.